Unforeseen benefits: outcomes of the Qanuinngitsiarutiksait study. Issue 1 (31st December 2022) - McDonnell, Leah; Lavoie, Josée G.; Clark, Wayne; Dutton, Rachel; Anawak, Caroline; Anawak, Jack; Brown, Levinia; Clark, Grace; Evaluardjuk-Palmer, Maata; Ford, Frederick
ABSTRACT: Scientific publications predominantly focus on research outcomes. Increasingly, community partnerships and relationships are mentioned, especially in research conducted with Indigenous communities. In partnership-based research, Indigenous communities expect researchers to contribute in a multitude of ways that go beyond doing research . This article reports on a series of unforeseen, yet positive contributions realised in the Qanuinngitsiarutiksait study, undertaken between 2015 and 2021. These contributions are different from the main outcomes of the study. Salient unforeseen benefits included the strengthening of the Manitoba Inuit community through hosting community feasts, games, and virtual events; creating opportunities to increase the visibility of Inuit Elders at University public events; supporting the growth of the Manitoba Inuit Association in terms of staff, programmes, and presence at provincial policy tables; leveraging relationships towards the development of Inuit-centric primary healthcare services in Winnipeg; creating a method to identify Inuit in provincial administrative datasets which were used to track COVID-19 infection rates and ensure equity in access to testing and vaccines. As a result, the Manitoba Inuit Association's visibility has increased, and Inuit Elders have become essential contributors of Indigenous knowledge at Manitoba-based events, as First Nations and Metis have been for decades. This transformation appears to be sustainable.